Torna-se ipãntuw: construção das relações de parentesco entre os Krahô e os não indígenas - Pedroso, Maíra (2023)
This dissertation presents an ethnography of the construction of kinship relations between the Krahô (mẽhĩ) and non-indigenous people (cupẽ). The Krahô are a Timbira people, from the Jê linguistic family, Macro-Jê trunk, who inhabit the Cerrado of Tocantins. In dialogue with the myth of Awkê and the history of contact between the Krahô and non-indigenous, this ethnography seeks to understand the place the non-indigenous occupies in Krahô thought and the possibilities of making them a relative by inserting them in their networks of kinship and alliance. In this sense, the way in which the cupẽ are inserted in Krahô society through onomastics (gaining a mẽhĩ name) and the participation in ritual life is highlighted. The present ethnography covers my history of kinship with the Krahô, throughout the transformations and learning that took place over the years in which we lived as kin to each other.